2014
DOI: 10.12691/ajbr-2-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sitagliptin and Glimepiride on Glucose Homeostasis and cAMP Levels in Peripheral Tissues of HFD/STZ Diabetic Rats

Abstract: Introduction: T2DM is a group of metabolic disorders manifested by hyperglycemia as a result of insulin insufficiency and/or resistance. The main goal of antidiabetic therapies is to lower glucose levels, and therefore prevent development of diabetes complications. DPP-4 inhibitors (e.g. sitagliptin) are relatively new antidiabetic drugs which inhibit the activity of DPP-4 enzyme and therefore prevent rapid degradation of incretin hormones. Objective: We investigated effects of sitagliptin on glucose homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Parallel to the changes in blood glucose level in the different studied groups, serum insulin showed significant reduction in untreated diabetic group compared to control rats, in accordance with [37][38][39], who reported a reduced serum insulin level in HFD/STZ rat model of type 2DM, and in controversy with the study of Saad et al [40] in which the diabetic rats exhibited significantly high serum insulin in the same rat model. The suggested explanation for this controversy may be the duration of HFD feeding in the aforementioned study.…”
Section: Discussionsupporting
confidence: 83%
“…Parallel to the changes in blood glucose level in the different studied groups, serum insulin showed significant reduction in untreated diabetic group compared to control rats, in accordance with [37][38][39], who reported a reduced serum insulin level in HFD/STZ rat model of type 2DM, and in controversy with the study of Saad et al [40] in which the diabetic rats exhibited significantly high serum insulin in the same rat model. The suggested explanation for this controversy may be the duration of HFD feeding in the aforementioned study.…”
Section: Discussionsupporting
confidence: 83%
“…In lipolytically active adipocytes, elevated intracellular cyclic adenosine monophosphate (cAMP) levels following hormonal stimulation result in phosphorylation of perilipin which rapidly initiates lipolysis of triglycerides to glycerol and fatty acids by phosphorylated HSL. Previously, our lab demonstrated that the diabetic state differentially affects cAMP levels according to the type of adipose tissue; WAT showed increased cAMP level, while BAT showed a decline in cAMP level [ 22 ]. Moreover, unrestrained lipolysis increases circulating levels of NEFA in the absorptive state, the driving force of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, BAT of diabetic rats showed elevated perilipin which could be explained by the fact that BAT is more insulin sensitive than WAT [ 24 ] and may retain insulin sensitivity even under insulin resistance. This declined cAMP and elevated perilipin levels in BAT may result in shifting in its metabolic capacity from lipolytic and catabolic into lipogenic and anabolic pathways which could change cells phenotype from BAT (metabolically active) into WAT (storage) phenotype [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One week after injection, fasting blood glucose (FBG) levels were determined from tail blood using an Accu-Chek Active glucometer (Roche Diagnostics, Manheim, Germany). The rats with FBG levels above 200 mg/dL were considered as diabetic [ 10 ]. Group (2) served as the diabetic untreated rats and were administered DMSO as a vehicle without any treatments.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the treatment period, the rats were fasted overnight, anaesthetized with diethyl ether, and sacrificed by cervical decapitation. The blood was collected for serum separation and biochemical analysis [ 10 ].…”
Section: Methodsmentioning
confidence: 99%